Reparation effects of vacuum wound therapy in patients with diabetic foot syndrome. - Besedin, A. M. (Medicni Perspektivi, 2015)
Vacuum Therapy (Vacuum-assisted closure, VAC) - a method of complex therapy which is used to improve the healing of both acute chronic wounds in patients with diabetic foot syndrome. Due to widespread introduction of this technique, unique cell, extracellular and general effects of its use in the treatment of patients with purulent-necrotic complications of diabetic foot syndrome, a technique of vacuum wound therapy has been successfully used in many surgical departments of Ukraine. Despite the diversity of the clinical effects of VAC-therapy and appearance of number of publications, in the domestic and foreign literature physiological basis of this method have not been studied completely. The effectiveness of vacuum therapy explain: the reduction of the size of the wound, the stabilization of the wound environment (due to the removal of inflammatory mediators and cytokines), microdeformation and remodeling of cell, rows reduction of edema, reduction of bacterial contamination, etc. At the same time, mechanisms of blood flow enhancement at different duration of VAC-therapy use, remain unclear its effect on the third phase of wound healing process as well.